A new approach for the pistoning measurement in transtibial prosthesis - Gholizadeh, Hossein; Abu Osman, Noor Azuan; Luviksdottir, Asa Gulaug; Eshraghi, Arezoo; Kamyab, Mojtaba; Wan Abas, Wan Abu Bakar (SAGE Publications, 2011)
Background: Good suspension lessens the pistoning (vertical displacement) of the residual limb inside the prosthetic socket. Several methods are used for measuring the pistoning. Study Design: Clinical trial. Objectives: To introduce and evaluate a new simple method for measuring the pistoning between the soft liner and socket in transtibial prostheses. Methods: Five transtibial prostheses with Iceross silicone liner and shuttle lock were made for the subjects. The pistoning was measured between the liner and socket by a photographic method in single limb support on the prosthetic limb (full weight bearing), non-weight bearing and under three static axial loading conditions (30, 60 and 90 N). Results: This new method enabled us to measure the pistoning between the liner and prosthetic socket. The reproducibility of measurements in different trials of one session and between two sessions by two observers was shown to be high. The average of displacement between the liner and socket was about 9 mm in non-weight bearing compared with full weight bearing. Furthermore, as we expected, the average of pistoning increased consistently by adding the loads. Conclusions: This new method provides for easy and inexpensive determination of pistoning between the liner and socket by every prosthetist in clinical settings. Â© The International Society for Prosthetics and Orthotics 2011.